ICT Supported Interventions for Occupational Stress Management: Theory to Practice - Weerasekara, M.K. (NSBM Green University, 2018)
Occupational stress has become a key source of stress among working population which has created numerous negative impacts on the community and of worldwide organizations, and they are expected to become a major health hazard in the forthcoming decades. During the investigation, the researcher will aim to identify the work- stress indicators and their impact on employee job performance. The study will also examine how employees cope with occupational stress whether the coping strategies are positive or negative. During the next round the researcher will design and develop ICT supported stress intervention toolkit for occupational stress management. ICT Supported health intervention is a phenomenon that has grown stronger in recent years. A large number of web and mobile-based health communities/applications has contributed to a shift: from formal healthcare providers being the only source of help for most patients to a situation in which patients take an active part in each other’s struggle for health and recovery. Also, for people with different lifestyle issues, the health communities have become widely used for advice and support. Through the interaction with others, patients and other people with health concerns can get help to access relevant resources, develop their ability to make personal decisions and exercise critical thinking. They get support to develop skills and abilities along with a more positive self-image. This is also referred to as ‘patient empowerment.
Keywords: occupational stress; ict; digital; web; mobile; intervention; design concepts